The application of lesion sterilization and tissue repair 3Mix-MP for treating rat's dental pulp tissue - Raditya Nugroho; Ananta Tantri Budi; Sri Kunarti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Lesion sterilization and tissue repair (LSTR) 3Mix-MP are three broad-spectrum antibiotics, including metronidazole, ciprofloxacin and minocycline are mixed with propylene glycol or macrogol. There is the possibility ofthe healing process that marked proliferation ofnew blood vessels and proliferation offibroblasts in the treatment ofirreversible pulpitis by pulp capping LSTR 3MixMP because of the principle of the method LSTR 3Mix-MP is to kill bacteria. Purpose: The purpose of this study to prove the effect of LSTR 3Mix-MP on chronic inflammation and the healing process in rat dental pulp tissue in vivo. Methods: Rattus norvegicus anaesthetized by using ketamine and xylazine dissolved in sterile isotonic saline solution (0.2 ml/50gr mm) on the upper right thigh. Cavity preparation class I to perforation by using a low speed tapered diamond round bur. In the treatment group, rats were treated 3Mix-MP at a dose of10 mg and then covered with glass ionomer cement for 7 days on the pulp that has been opened for 3 days. The control group treated with saline irrigation on the pulp that has been opened for 3 days. Rats were killed after seven days, and then made preparations pulp tissue to count the number oflymphocytes, macrophages, plasma cells, blood vessels, and fibroblasts Results: There is an increase in the average number ofmacrophage cells, plasma, and fibroblasts; and decreased lymphocytes and blood vessels in the treated group exposure LSTR 3Mix-MP. Conclusion:LSTR 3Mix-MP can reduce chronic inflammation process and enhance the healing process in rat dental pulp tissue.